Novel point mutations in the dihydrofolate reductase gene of Plasmodium vivax: evidence for sequential selection by drug pressure. - Imwong, M; Pukrittayakamee, S; Rénia, L; Letourneur, F; Charlieu, J; Leartsakulpanich, U; Looareesuwan, S; White, N; Snounou, G (2003)
Mutations in the dihydrofolate reductase (dhfr) genes of Plasmodium falciparum and P. vivax are associated with resistance to the antifolate antimalarial drugs. P. vivax dhfr sequences were obtained from 55 P. vivax isolates (isolates Belem and Sal 1, which are established lines originating from Latin America, and isolates from patient samples from Thailand [n = 44], India [n = 5], Iran [n = 2], and Madagascar [n = 2]) by direct sequencing of both strands of the purified PCR product and were compared to the P. vivax dhfr sequence from a P. vivax parasite isolated in Pakistan (isolate ARI/Pakistan), considered to represent the wild-type sequence. In total, 144 P. vivax dhfr mutations were found at only 12 positions, of which 4 have not been described previously. An F-->L mutation at residue 57 had been observed previously, but a novel codon (TTA) resulted in a mutation in seven of the nine mutated variant sequences. A new mutation at residue 117 resulted in S-->T (S-->N has been described previously). These two variants are the same as those observed in the P. falciparum dhfr gene at residue 108, where they are associated with different levels of antifolate resistance. Two novel mutations, I-->L at residue 13 and T-->M at residue 61, appear to be unique to P. vivax. The clinical, epidemiological, and sequence data suggest a sequential pathway for the acquisition of the P. vivax dhfr mutations. Mutations at residues 117 and 58 arise first when drug pressure is applied. Highly mutated genes carry the S-->T rather than the S-->N mutation at residue 117. Mutations at residues 57 and 61 then occur, followed by a fifth mutation at residue 13.